Dopamine agonist-responsive Cushing's disease. Issue 2 (13th February 2019) - Anand, Gurpreet; Bink, Andrea; Beuschlein, Felix; Schmid, Christoph
Abstract : A 47-year-old Caucasian man was referred to our clinic with a severe clinical and biochemical phenotype of endogenous hypercortisolism for further evaluation and treatment. In addition to confirming adrenocorticotropic hormone (ACTH)-dependent Cushing's syndrome, we found left temporal hemianopsia, massively increased prolactin, increased growth hormone/insulin-like growth factor 1 values, hypogonadotropic hypogonadism and central hypothyroidism. As the cause of these abnormalities we revealed an invasive macroadenoma of the pituitary secreting ACTH, prolactin and growth hormone, resulting not only in a clinically predominant picture of Cushing's syndrome but also causing hypogonadotropic hypogonadism and central hypothyroidism. The patient responded surprisingly well to dopamine agonist treatment leading not only to normalisation of prolactin levels but also to clinical and biochemical remission of Cushing's syndrome. Tumour size decreased successively in follow-up MRI scans. Despite lacking immunohistochemical analysis of tumour tissue, we assume plurihormonal secretion of ACTH, prolactin and growth hormone from pituitary macroadenoma, which fortunately responded well to dopamine agonist treatment.